2019
DOI: 10.1111/cpr.12595
|View full text |Cite
|
Sign up to set email alerts
|

Human dental pulp stem cells regulate allogeneic NK cells’ function via induction of anti‐inflammatory purinergic signalling in activated NK cells

Abstract: Objectives: Mesenchymal stem cells (MSCs) could regulate the function of various immune cells. It remains unclear whether MSCs additionally possess immunostimulatory properties. We investigated the impact of human MSCs on the responsiveness of primary natural killer (NK) cells in terms of induction of anti-inflammatory purinergic signalling. Material and Methods:We obtained human bone marrow mesenchymal stem cells (BMMSCs) and dental pulp stem cells (DPSCs). NK cells were isolated from peripheral blood of heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 45 publications
0
23
0
Order By: Relevance
“…Upon exposure to mesenchymal stem cells (MSCs), T cells upregulate CD39, resulting in suppression of activated T cells via increased production of extracellular adenosine (36). Similarly, studies reported that NK cells acquire the expression of CD73 after physical contact with human umbilical cord-derived MSCs or dental pulp stem cells (37,38). In cancer, NK cells from gastrointestinal stromal tumors (GISTs) have been found to express higher levels of surface CD73 (39).…”
Section: Nk Cell Signature Influences the Predictive Value Of Cd73 Gementioning
confidence: 99%
“…Upon exposure to mesenchymal stem cells (MSCs), T cells upregulate CD39, resulting in suppression of activated T cells via increased production of extracellular adenosine (36). Similarly, studies reported that NK cells acquire the expression of CD73 after physical contact with human umbilical cord-derived MSCs or dental pulp stem cells (37,38). In cancer, NK cells from gastrointestinal stromal tumors (GISTs) have been found to express higher levels of surface CD73 (39).…”
Section: Nk Cell Signature Influences the Predictive Value Of Cd73 Gementioning
confidence: 99%
“…As a result, NK cells increased their ability to convert AMP into Ado 207 . Later, two further studies confirmed these findings 65,69 . Yan et al 65 showed that NK cells cocultured with the DP‐MSCs in a transwell system exhibited higher CD73 expression in comparison with the control cells.…”
Section: Adenosinergic Signaling In Immunomodulatory Effects Of Mscsmentioning
confidence: 84%
“…The adenosinergic pathway emerges as a key mechanism by which MSCs exert hemostatic and immunomodulatory functions. Depending on the CD73/adenosine pathway, MSCs inhibited platelet activation and aggregation (Netsch et al, 2018), altered T-cell activation (Chen et al, 2016), and reduced NK cell activity (Yan et al, 2019). Of note, NK cells interacting with MSCs may acquire the expression of external nucleotide CD73.…”
Section: Regulation Of Metabolic Pathwaysmentioning
confidence: 99%